Métodos anticonceptivos y el embarazo precoz en adolescentes que se atenderán en el hospital III EsSalud, Iquitos 2023 - Gonzales Rengifo, Gabriel (2025)
The present investigation is titled "CONTRACEPTIVE METHODS AND EARLY PREGNANCY IN ADOLESCENTS WHO WILL BE ATTENDED AT HOSPITAL III ESSALUD, IQUITOS 2023", it was oriented with the objective of knowing if there is a relationship between contraceptive methods and early pregnancy in adolescents who are They will attend Hospital III EsSalud, Iquitos 2023. The methodology that will be used in this research will be descriptive, observational with a cross section with a correlational level with a non-experimental design. The population will be made up of 100 pregnant adolescents who will be treated at Hospital III EsSalud in the capital of Iquitos, the sampling method will be intentional non-probabilistic, so the sample will be 60 pregnant adolescents who will be attended at Hospital III EsSalud, Iquitos 2023. The technique used will be the survey and its instrument the questionnaire. To carry out the processing of the data and the presentation will be made with tables and figures with their respective analysis and interpretation.